Oncogenic miR-146a-PBX2 axis, a novel leukemic target in xenograft acute lymphoblastic leukemia model - Shahid, Samiah; Javed, Maryam; Shahid, Wajeehah; Asif, Roha; Liaqat, Ambreen; Nisar, Haseeb; Mehreen, Saba (International Journal of Applied and Experimental Biology, 2024)
Acute lymphoblastic leukemia (ALL) is one of the major hematological malignancies both in adults and children. Bone marrow biopsy is the main requirement for its accurate diagnostic and prognostic purpose till now that is a very painful process especially for children. The reluctance to go for bone marrow biopsy leads to delayed diagnosis treatment of ALL. MicroRNAs are emerging as diagnostic and therapeutic targets for cancer including ALL using less painful methods. The current study was conducted to evaluate the potential of miR-146a-PBX2 axis as a leukemic target of ALL using ALL-induced rabbit model. A total of 8 rabbits were divided into two groups: ALL-induced (diseased) and normal (control). The whole blood was collected from both groups and plasma isolation was performed. The levels of miR-146a and PBX2 gene in plasma of diseased and control samples were quantified by the real-time PCR (RT-qPCR). The normalized fold expression was calculated using miR-16 and the reference gene GAPDH. The results showed that there was a significant increase in miR-146a expression in diseased (ALL-induced) samples as compared to the control. Moreover, a significant upregulation of PBX2 gene was found in the diseased model as compared to that in the control. The results implied that miR-146a-PBX2 axis may be utilized as a potential target for ALL.